A study on market interdependencies of stock market among Southeast Asia in term of small capital - Ismail, Nur Atikah (2012)
The purpose of this paper to investigate the market interdependencies as well as the correlation between Indonesia Stock Exchange (IDX), Straits Times Index (STI), and Stock Exchange of Thailand (SET) to the FTSE Bursa Malaysia in term of small capital. The weekly return from 1st January 2007 until 30th December 2011 was employed in the Single Linear Regression Model and Multiple Linear Regression Model. The data used in this study are limited to the small capital market located in Southeast Asia that concentrating more on Indonesia stock market, Singapore stock market, and Thailand stock market. Further research may be conducted using a different time period and frequency of data while utilizing more small capital indices. In addition, future research may look at and compare the market interdependence of small capital market in different stock market and economic condition such as the pre-economic crisis period, during an economic crisis period, or post-economic crisis period.